Around the world in 80 days - MCFADDEN, DEANNA; DEANNA MCFADDEN (New York Sterling Publishing, 2007)
English gentleman Phileas Fogg bets £20,000 that he can circumnavigate the globe in exactly 80 days. Accompanied by his loyal servant Passepartout, Fogg travels via steamship and rail through Asia and America, overcoming obstacles and a mistaken police pursuit to return to London just in time.
Keywords: a classic adventure novel that follows the journey of Phileas Fogg, a wealthy, meticulous, and habitually punctual English gentleman, as he attempts to circumnavigate the globe in 80 days; perseverance, precision, and the value of human connection over strict scheduling